Efeito do creme de jambu (acmella oleracea) sobre a função sexual masculina e feminina - Regadas, Rommel Prata (2008)
The toothache plant (Spilanthes oleracea or Spilanthes acmella oleracea or simply Acmella oleracea) is a well-known herb in Northern Brazil, especially in Pará, where it is referred to as jambu. Though commonly used in the local cuisine in dishes such as tacacá and pato-no-tucupi, it is also widely used to prepare analgesic, antiinflammatory and antifungal medications. Extracts of this plant have recently become popular as a topical sexual stimulant for women. The active substance in the herb, spilanthol, is believed to contract the vulva, but so far no medical study has been published confirming this. In the present randomized, double-blind, placebo-controlled crossover clinical study a cream was prepared from extracts of the toothache plant and tested with regard to its effect on female sexual desire and excitation and male sexual desire and satisfaction and ejaculation time, along with safety and tolerability. Twenty-two blinded couples used cream with and without extract of A. oleracea during two periods of 4 weeks. The participants were aged 43.3 years (men) and 40.5 years (women) on the average and were evaluated individually using self-reported questionnaires (the International Index of Erectile Function and The Female Sexual Function Index) before and after the use of each cream. Compared to placebo, male sexual desire and satisfaction (p=0.0008 and p=0.0006, respectively) and female sexual desire and excitation (p=0.0006 and p=0.0005, respectively) were significantly greater when couples were using the extract. Likewise, male sexual desire and satisfaction (p=0.0002 and p=0.0003, respectively) and female sexual desire and excitation (p=0.0001 and p=0.0008, respectively) only increased in relation to baseline values when couples were using extract. No significant differences were observed between extract and placebo with regard to ejaculation time (p=0.7768), nor with regard to pain and discomfort after intercourse, as reported by both genders (p=0.7728 and p=1.0000, respectively). It may be concluded that cream prepared from extracts of the toothache plant increased female sexual desire and excitation and male sexual desire and satisfaction during intercourse compared to placebo and baseline, without affecting ejaculation time. Side effects were negligible and subsided after completion of treatment.